2019
DOI: 10.1055/s-0037-1611722
|View full text |Cite
|
Sign up to set email alerts
|

A Concise, Catalyst-Free Synthesis of Davis’ Oxaziridines using Sodium Hypochlorite

Abstract: N-Sulfonyloxaziridines (Davis’ oxaziridines) can be synthesized by reacting the corresponding N-sulfonylimines with aqueous sodium hypochlorite in acetonitrile without any catalyst. The pH of the aqueous sodium hypochlorite is crucial to obtain the product in high yield. Optimized conditions are presented that allow synthetically useful Davis’ oxaziridines to be easily obtained in up to 90% yields from the corresponding imines by using inexpensive, stable, environmentally friendly sodium hypochlorite pentahydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The synthesized compounds (25) were employed to oxidize sulfides. [26,27] It was revealed that due to the presence of trichloromethyl (23) and nitro groups (25) on the dihydroisoquinoline skeleton, the oxaziridine became more electrophilic and the reaction of oxygen transfer into sulphide occured in absence of acid (see section 3.1.2).…”
Section: N-sulfonyl Oxaziridines and Dihydroisoquinoline Oxaziridinesmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesized compounds (25) were employed to oxidize sulfides. [26,27] It was revealed that due to the presence of trichloromethyl (23) and nitro groups (25) on the dihydroisoquinoline skeleton, the oxaziridine became more electrophilic and the reaction of oxygen transfer into sulphide occured in absence of acid (see section 3.1.2).…”
Section: N-sulfonyl Oxaziridines and Dihydroisoquinoline Oxaziridinesmentioning
confidence: 99%
“…developed a catalyst‐free, environment‐friendly method towards the Davis oxaziridines 20 via the reaction of N ‐sulfonyl imines 19 with sodium hypochlorite (NaOCl) in aqueous acetonitrile under basic conditions (Scheme 7). [23] …”
Section: Direct Synthesis Of Oxaziridinesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, aq NaOCl was useless for the oxidative cleavage of cis- and trans- 1a (Table , runs 1–4). The reaction of these compounds with NaOCl·5H 2 O was next approached because we recently have reported that NaOCl·5H 2 O is a superior reagent to conventional aq NaOCl in the oxidation of organic compounds . For comparison, we also examined the reaction with conventional reagents including sodium periodate (NaIO 4 ), Pb­(OAc) 4 and PhI­(OAc) 2 .…”
mentioning
confidence: 99%
“…Although conventional aq NaOCl has been used as an oxidant for glycol cleavage, it is not effective in cleaving highly hindered bicyclic glycol 1a , as shown in Table (runs 1–4). This is because aq NaOCl is not effective enough to have a high pH value (>13) compared to the low pH (10–11) of NaOCl·5H 2 O crystals in several oxidation reactions . Therefore, the effect of pH on the glycol cleavage reaction was examined using 1e as a substrate (Table ).…”
mentioning
confidence: 99%